Colors and blood : flag passions of the Confederate South - Bonner, Robert E., 1967- (Princeton University Press, 2002)
"As rancorous debates over Confederate symbols continue, Robert Bonner explores how the rebel flag gained its enormous power to inspire and repel. In the process, he shows how the Confederacy sustained itself for as long as it did by cultivating the allegiances of countless ordinary citizens. Bonner also comments more broadly on flag passions - those intense emotional reactions to waving pieces of cloth that inflame patriots to kill and die."--Jacket